2020
DOI: 10.1002/jper.19-0107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dehiscence‐type defects with collagen matrix and/or enamel matrix derivative: Histomorphometric study in minipigs

Abstract: BackgroundThis study aimed to evaluate, histomorphometrically, the use of collagen matrix (CM) and/or enamel matrix derivative (EMD) for the treatment of dehiscence‐type recession defects in minipigs.MethodsEight healthy, male, young BR‐1 minipigs, with no periodontal disease were treated. Bilateral dehiscence‐type defects were surgically created on the buccal of the mandibular premolars (PI and PII). After 30 days, the defects were randomly assigned to four groups: coronally advanced flap (CAF); CAF + CM; CAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The early and long-term healing results in the present study were similar to those of França-Grohmann et al ( 2020), who reported that the use of EMD in periodontal regeneration increased the new cementum and new bone formation in an experimental study in minipigs (França-Grohmann et al, 2020). Other experimental studies reported similar results regarding the effectiveness of EMD for periodontal regeneration (Casati et al, 2002;Sallum et al, 2004;Takeda et al, 2018).…”
Section: Ta B L E 1 Histomorphometric Findingssupporting
confidence: 91%
“…The early and long-term healing results in the present study were similar to those of França-Grohmann et al ( 2020), who reported that the use of EMD in periodontal regeneration increased the new cementum and new bone formation in an experimental study in minipigs (França-Grohmann et al, 2020). Other experimental studies reported similar results regarding the effectiveness of EMD for periodontal regeneration (Casati et al, 2002;Sallum et al, 2004;Takeda et al, 2018).…”
Section: Ta B L E 1 Histomorphometric Findingssupporting
confidence: 91%
“…16,19,20 In addition, because the matrices have different manufacturing processes that lead to different structural and physical characteristics, they may have different outcomes. 22,23 Thus, the aim of the present study was to evaluate the superiority of clinical and patient-centered outcomes of two types of XM (both associated with the CAF technique) versus CAF alone to treat single gingival recession, as well as to make direct comparisons and evaluate whether one of the matrices is superior to the other.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of an enamel matrix derivative (EMD) has been proposed to improve the effectiveness of soft tissue coverage of exposed root surfaces [5]. Studies showed that CAF combined with sCTG or EMD increases the probability of achieving complete root coverage (CRC) in Miller class I and II [6] and Cairo type I [7] recession defects compared to CAF alone [8][9][10]. The satisfying results achieved with the use of EMD have encouraged clinicians to introduce another organic molecule in periodontal therapy, namely hyaluronic acid (HA).…”
Section: Introductionmentioning
confidence: 99%